Równość versus sprawiedliwość - Bartula, Piotr (Annales. Etyka w Życiu Gospodarczym, 2014)
On the example of a workload dispute (a version of a ‘border dispute’)I present the general problem of two persons – M and P – with equal entitlementsto one commodity, which is equally desired by both of them. They are both moderatelyaltruistic; they are not angels untempted by a selfish willingness to gettheir own way, nor are they devils, who want to destroy others even if it leads toself-destruction. As human beings operating in a world of limited goods, they areso physically and intellectually feeble that neither of them is able to permanentlyenslave the other and submit him to the second person’s will.Such being the case, each solution to the problem means that the profit of oneperson is the loss of the second. The question, whether justice is possible at all,suggests itself whether in a situation when people are more or less equal, or withlimited altruism and/or selfishness and scarce resources.